2017
DOI: 10.1016/j.athoracsur.2017.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Concepts Applied in Congenital Heart Disease and Cardiac Surgery

Abstract: All biological processes are governed by principles of physics that dictate the pathophysiology and even the treatment of congenital heart diseases. In this review, basic concepts such as flow, pressure, resistance, and velocity are introduced, followed by more complex laws that describe the relationship between these variables and the disease processes. Finally, physical phenomena such as turbulence, steal and runoff phenomenon, and energy loss are discussed. By application of these principles, one can accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Lower wall shear stress (WSS), a product of WSR and plasma viscosity, has previously been associated with upregulation of hypoxia-inducible factor 1 α (HIF1α) and tissue hypoxia (Feng et al, 2017) in porcine and murine arteries. Reductions in WSS are seen in conditions with reduced flow or flow turbulence (Papaioannou et al, 2005) and have been reported in patients with aortic aneurysm (Raghavan et al, 2000) and congenital subaortic stenosis (Cape et al, 1997;Gerrah et al, 2017). We reported a significantly lower overall mean WSR for the CCHD patients, again with the most significant differences observed for group 4 vessels (the most prevalent).…”
Section: Cchd-cyanotic Congenital Heart Disease 4 Discussionsupporting
confidence: 73%
“…Lower wall shear stress (WSS), a product of WSR and plasma viscosity, has previously been associated with upregulation of hypoxia-inducible factor 1 α (HIF1α) and tissue hypoxia (Feng et al, 2017) in porcine and murine arteries. Reductions in WSS are seen in conditions with reduced flow or flow turbulence (Papaioannou et al, 2005) and have been reported in patients with aortic aneurysm (Raghavan et al, 2000) and congenital subaortic stenosis (Cape et al, 1997;Gerrah et al, 2017). We reported a significantly lower overall mean WSR for the CCHD patients, again with the most significant differences observed for group 4 vessels (the most prevalent).…”
Section: Cchd-cyanotic Congenital Heart Disease 4 Discussionsupporting
confidence: 73%
“…We hypothesize that runoff from severe AI led to significant flow reversal in the LCA secondary to a Venturi effect in the left aortic sinus of Valsalva. 4,5 This has been demonstrated in an experimental model in dogs, whereby injury of the left aortic cusp led to a regurgitant stream near the coronary ostium, leading to diastolic flow reversal in the LCA. 5 A left aortic cusp anomaly leading to myocardial ischemia has previously been reported in two cases.…”
Section: Commentmentioning
confidence: 95%
“…For example, in clinical applications, velocity carries significant importance and is often used as a surrogate to quantify flow, pressure, or the cross-sectional area of a structure through which blood flows through, based on Bernoulli’s equation. 1 For instance, a higher velocity means passage of blood through a narrower area. Conversely, CFD allows direct calculation of pressure and velocity simultaneously, with the ability to visualization of these dynamics in a 3D structure view of a patient-specific model.…”
Section: Introductionmentioning
confidence: 99%